RENCANA BISNIS SUPPLIER STOCKLOT PAKAIAN BRANDED (Stocklot Supplies Business Plan Of Brande Clothes) - Saputra, Rahmat Bagus; Suwandi, Suwandi (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
This business plan is made to explain: 1) how Mottoup Store can be developed from the situation that has been running since December 2018, 2) Market strategy so that the products sold are better known to the public so as to increase sales. 3) Human resources who will run this business, 4) Funding requirements, rate of return and risk. Several analytical tools are used, namely: STP (Segmenting, Targeting, Positioning), Five Forces Porters, SWOT analysis, Business Model Canvas (BMC) and risk analysis. From the analysis it was concluded that this business plan is prospective and feasible to run.